2005
DOI: 10.1002/eji.200425902
|View full text |Cite
|
Sign up to set email alerts
|

Substance P regulates natural killer cell interferon‐γ production and resistance to Pseudomonas aeruginosa infection

Abstract: Studies have shown that after Pseudomonas aeruginosa (P. aeruginosa) corneal infection, BALB/c mice that are capable of resolving the disease, locally produce IFN-c. As T cells are not detected in the infected cornea of these mice, antibody depletion was used to test whether NK cells produce the cytokine. After depletion, decreased corneal IFN-c mRNA and increased disease severity, bacterial load, and PMN infiltrate resulted. Further work determined if substance P (SP), a pro-inflammatory neuropeptide, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 39 publications
(43 reference statements)
0
55
0
Order By: Relevance
“…The reduced level of IFN-g in the lung of naive mice after transfer of CLP-BMDC (Fig. 6B) equals the disturbed IFN-g production in the lung of P. aeruginosa-infected post-septic mice (28,30). This observation points to a role of NK cells in the CLP-BMDC-mediated immunosuppression.…”
Section: Cd8mentioning
confidence: 67%
See 1 more Smart Citation
“…The reduced level of IFN-g in the lung of naive mice after transfer of CLP-BMDC (Fig. 6B) equals the disturbed IFN-g production in the lung of P. aeruginosa-infected post-septic mice (28,30). This observation points to a role of NK cells in the CLP-BMDC-mediated immunosuppression.…”
Section: Cd8mentioning
confidence: 67%
“…6D, 6E) argues against a negative effect of CLP-BMDC on granulocyte recruitment. NK cells represent the major source of IFN-g in the lung upon P. aeruginosa infection (23), and protective immunity against these microbes is associated with the expression of IL-12 and IFN-g (28,29). The reduced level of IFN-g in the lung of naive mice after transfer of CLP-BMDC (Fig.…”
Section: Cd8mentioning
confidence: 99%
“…In general, control of an inflammatory state depends on the regulation of immune cells, such as macrophages (M ) 3 and polymorphonuclear neutrophils (PMN), as well as the local balance between pro-and antiinflammatory factors released by these and other host cells. Immunoregulation is even more consequential in light of ocular immune privilege and the subsequent conservation of the visual field and these inflammatory events can be characterized using murine models of ocular inflammatory disease.…”
mentioning
confidence: 99%
“…Previous studies using the susceptible/resistant models have provided essential information regarding the roles of inflammatory cells (e.g., PMN, T cells, M , and Langerhans cells), as well as cytokines and chemokines in modulating inflammation, innate immunity, and Th1-vs Th2-like responses to P. aeruginosa in the eye (1). Yet, little information is available regarding the roles of neuropeptides in this disease (3), despite the fact that the cornea is among the most densely innervated tissues in the body (4).…”
mentioning
confidence: 99%
“…The incomplete protection based on survival in the NK1R antagonisttreated animals may be due to the incomplete action of the NK1R antagonist as the levels of substance P rise in the infected, sympathectomized mice outcompetes for NK1R activation or the dual role of substance P associated with pain perception (Lundy and Linden, 2004) as well as an immunomodulator. For example, substance P elicits the production of cytokines including TNF-α (Lotz et al, 1988), and IFN-γ (Lighvani et al, 2005) which are linked to the control of HSV-1 infection. As T and B lymphocytes and monocyte/macrophages express the NK1R (Stanisz et al, 1987;Pascual et al, 1992;Marriott and Bost, 2000), it has been suggested substance P may serve to optimize the local inflammatory response (Marriott and Bost, 2000) which may facilitate the clearance of pathogens (Brogden et al, 2005;Svensson et al, 2005) but have detrimental consequences relative to sites sensitive to inflammation as is the case of rheumatoid arthritis (Miller et al, 2000) and most likely, the CNS.…”
Section: Discussionmentioning
confidence: 99%